2013
DOI: 10.1111/apha.12189
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic look at the effects of adversity early in life on cardiovascular disease risk during adulthood

Abstract: Early origins of adult disease may be defined as adversity or challenges during early life that alter physiological responses and prime the organism to chronic disease in adult life. Adverse childhood experiences or early life stress (ELS) may be considered a silent independent risk factor capable of predicting future cardiovascular disease risk. Maternal separation (Mat-Sep) provides a suitable model to elucidate the underlying molecular mechanisms by which ELS increases the risk to develop cardiovascular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 124 publications
1
37
0
Order By: Relevance
“…The studies by Pollock and coworkers showed that rats exposed to this ELS had normal resting BP as adults but exaggerated acute pressor (vasoconstrictor) responses to norepinephrine (37) and augmented hypertensive responses to chronic angiotensin II infusion (39,40). Their studies implicated changes in arterial and kidney function in the relationship between ELS and adult hypertension (38). In the present study, we observed that PND21 MA1s from rats exposed to MS stress at PND2-14 had increased force to KCl depolarization, to PE, and to calcium in permeabilized preparations, all consistent with the acceleration of the functional maturation of these arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The studies by Pollock and coworkers showed that rats exposed to this ELS had normal resting BP as adults but exaggerated acute pressor (vasoconstrictor) responses to norepinephrine (37) and augmented hypertensive responses to chronic angiotensin II infusion (39,40). Their studies implicated changes in arterial and kidney function in the relationship between ELS and adult hypertension (38). In the present study, we observed that PND21 MA1s from rats exposed to MS stress at PND2-14 had increased force to KCl depolarization, to PE, and to calcium in permeabilized preparations, all consistent with the acceleration of the functional maturation of these arteries.…”
Section: Discussionmentioning
confidence: 99%
“…ELS can significantly modulate components of the hypothalamic-pituitary-adrenal (HPA) axis and the sympathetic-adrenal-medullary (SAM) system in rodents (20). Specifically, rodents that have been subjected to maternal separation before weaning show altered circulating plasma corticosterone levels, increased HPA axis responsiveness to stressors, altered hippocampal glucocorticoid receptor density, increased corticotropin-releasing factor expression in hypothalamus, and decreased serotonin transporter and tryptophan hydrolyase expression in Table 2 for statistical analyses (n ϭ 5-7 per group).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, sensitivity to vasoactive factor Ang II is enhanced following this developmental insult. Female ELS offspring exhibit a delay in the development of Ang II-induced hypertension relative to male ELS (Figure 7) (115) Furthermore, the degree of Ang II-induced hypertension is attenuated in female ELS offspring compared to male ELS offspring (Figure 7) (115) indicating that sex impacts the programming of CV risk in this model of ELS. Therefore, females in this model, like that observed in models induced by nutritional insults, are protected to some degree relative to their male littermates.…”
Section: History and Etiology Of The Fetal Origins Of Cardiovascular DImentioning
confidence: 96%
“…However, chronic stress prior to conception increases the risk of low birth weight (201). In addition, psychosocial stress in early life can impact later CV and metabolic health (For review, see 115). The mechanisms that contribute to the racial disparities in the prevalence of low birth weight are not clear.…”
Section: History and Etiology Of The Fetal Origins Of Cardiovascular DImentioning
confidence: 99%
See 1 more Smart Citation